Strategi Peningkatan Penjualan Melalui Kepercayaan Konsumen Pada Shopee Live - Yuke Elbana Ar Rahman; Lina Fatimah Lishobrina; Affriza Brilyan Relo Pambudi Agus Putra (Universitas Multi Data Palembang, 2026)
The evolution of digital technology has significantly transformed consumer behavior, especially on Shopee, the leading e-commerce platform in Indonesia. To facilitate purchase decisions, Shopee incorporates interactive features like Live Streaming and Flash Sales. This study explores the function of consumer trust as a mediating variable in the connection between these features and the ultimate purchase decision. Utilizing a quantitative approach with an explanatory research design, data was gathered through questionnaires distributed to 250 Shopee users who had previously engaged with both the Live Streaming and Flash Sale features. The analysis of the data was conducted using SPSS, employing path analysis testing. The results indicate that both Live Streaming and Flash Sales positively and significantly affect consumer trust. Furthermore, consumer trust has a considerable influence on purchase decisions. Most notably, the findings establish that consumer trust serves as a significant mediator, linking the utilization of Live Streaming and Flash Sales to the consumer's buying decision. This research provides essential implications for e-commerce companies, emphasizing the importance of improving digital marketing strategies by utilizing interactive features to foster consumer trust, which subsequently drives purchasing decisions.